Investigation of state, trends and structure of the world market of nanopowders - Malyshev, Victor; Kushchevska, Nina; Korotieieva, Antonina; Bruskova, Diana-Maria; Lukashenko, Tetiana; Zalubovskiy, Mark (Technology audit and production reserves, 2018)
The object of research is the state, trends and structure of the global market of nanopowders. One of the most problematic places is the ambiguity of literary data on this subject. The systematization of available literary data will solve this problem. For the marketing analysis, method of searching for literature data concerning the research subject and method of analysis were used. The analysis of literary sources made it possible to identify nanomaterials as the most commercial sector of the modern nanotechnology market. Information is provided about the most common throughout the world nanopowders of metals and oxides, as well as about their application fields. It is shown that complex nanopowders consisting of mixtures of oxides have a limited usage scope. The composition, size, and shape of the nanopowders particles depend on the obtaining method and the process conditions. The forecast of the share of different countries in the market of nanopowders and of the potential demand for nanoproducts in the future is carried out. The structure of investments by industries and predicted volume of nanotechnology market were shown. The structure of the nanopowders market according to the directions of use and types of nanopowders is given. In the course of the research the method of systematization and classification were used. The data on the world-wide volume of nanopowders production by the nature of metals and the structure of their production by particle size are systematized. A common problem in the nanotechnology market is the high cost of production and low volume of production. The high cost of nanoparticles is determined by the high cost of raw materials and by a small volume of production. The nanopowders consumption volume is influenced by the nature of their industrial use. The structure of consumption of nanopowders by industries at the world level is shown, about 70 % of consumption is accounted for electronics, optics and defense industry. The systematization of literature data allowed to present the problems of nanopowders in the form of tables and diagrams giving certain advantage to the comprehension and use of the material.